2020
DOI: 10.1038/s41467-020-17315-0
|View full text |Cite
|
Sign up to set email alerts
|

MEPE loss-of-function variant associates with decreased bone mineral density and increased fracture risk

Abstract: A major challenge in genetic association studies is that most associated variants fall in the non-coding part of the human genome. We searched for variants associated with bone mineral density (BMD) after enriching the discovery cohort for loss-of-function (LoF) mutations by sequencing a subset of the Nord-Trøndelag Health Study, followed by imputation in the remaining sample (N = 19,705), and identified ten known BMD loci. However, one previously unreported variant, LoF mutation in MEPE, p.(Lys70IlefsTer26, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
0
15
0
Order By: Relevance
“…Furthermore, rs10668066 has been associated with heel bone mineral density in adults ( Kim, 2018 ; Kemp et al, 2014 ). In a recent GWAS study, Surakka et al reported that the intergenic WNT16 variant rs2707518 was one of ten genome-wide significant BMD-associated loci in the discovery HUNT dataset (N = 19,705) ( Surakka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, rs10668066 has been associated with heel bone mineral density in adults ( Kim, 2018 ; Kemp et al, 2014 ). In a recent GWAS study, Surakka et al reported that the intergenic WNT16 variant rs2707518 was one of ten genome-wide significant BMD-associated loci in the discovery HUNT dataset (N = 19,705) ( Surakka et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…These array versions have nearly identical 570K marker backbones synthesized in two batches. The array design contains customized probes incorporated to detect candidate variants from GWAS for multiple diseases and traits (∼2,700), nonsense and missense variants (∼49,000), ancestry informative markers (∼3,300), and Neanderthal variants (∼5,300) (Surakka et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…Following the genotyping of nearly 70 000 participants in HUNT2 and HUNT3 and the development of a combined HRC and HUNT-WGS imputation reference panel, we extended our analyses to a genome-wide search (Figure 5). Through imputation of indels called from low-pass HUNT-WGS, we discovered a rare mutation in the MEPE gene, enriched in the Norwegian population (0.8% in HUNT, 0.1% in non-Finnish Europeans), that was associated with low forearm bone mineral density and increased risk of osteoporosis and fractures 21 . Although this region had been previously identified as associated with bone mineral density 22 , the association in HUNT with replication in the UK biobank 23 pin-pointed MEPE as the likely causal gene in the region by identifying an insertion/deletion polymorphism that likely resulted in a loss-of-function protein.…”
Section: Genetic Discoveries From Huntmentioning
confidence: 99%